2018
DOI: 10.1016/j.dyepig.2017.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiadiazole derivatives functionalized with two different (hetero)aromatic donor groups: Synthesis and evaluation as TiO 2 sensitizers for DSSCs

Abstract: A series of benzothiadiazole-based push-pull heterocyclic systems were synthesized and characterized in order to study the variations induced by different aromatic and heterocyclic donor groups in the optical, electronic and photovoltaic properties of DSSCs prepared with the respective cyanoacetic acid derivatives. The organic sensitizers bear a 5-hexyl-2,2′-bithienyl or N,N-diphenylanilino donor moieties conjugated with a thienyl-benzothiadiazole spacer functionalized with the electron acceptor/anchoring cyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…On the other hand, for efficient electron injection, the energy state level (LUMO) should be above that of the conductivity band of TiO2 (4.0 eV) [39]. Considering the electrochemical data, it can be [37]. Compound 2a was characterized by a non-reversible oxidation process.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for efficient electron injection, the energy state level (LUMO) should be above that of the conductivity band of TiO2 (4.0 eV) [39]. Considering the electrochemical data, it can be [37]. Compound 2a was characterized by a non-reversible oxidation process.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…The oxidation process is important for compounds tested as dyes in DSSCs. The compounds should exhibit similar potential to the potential of the pair I 3 − /I − being 0.42 V, enabling the regeneration of dyes by I − in the electrolyte[37]. Compound 2a was characterized by a non-reversible oxidation process.After three scans, no product of electrode surface was found (FigureS14).…”
mentioning
confidence: 99%
“…A long-conjugated molecule forms from the structure, which broadens the longwavelength absorption spectrum. In the field of dye-sensitized solar cells, it is reported that benzothiadiazole-based dyes can match the simulated solar light [28][29][30][31]. In addition, 4,7-dibromo-2,1,3-benzothiadiazole is very reactive for nucleophilic substitution reactions and coupling reactions [32].…”
Section: Introductionmentioning
confidence: 97%
“…It is also well known that the position of the heterocyclic nuclei on the π-spacers is an important factor. Both types of heterocycles, electron-rich, such as thiophene and pyrrole, and electron-deficient, such as azole and azine derivatives, i.e., (benzo)thiazole benzothiadiazole, pyridine, etc., can act simultaneously as π-bridges and electron donors or acceptors, respectively [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%